The simultaneous detection of the squamous cell carcinoma antigen and cancer antigen 125 in the cervical cancer serum using nano-Ag polydopamine nanospheres in an SERS-based lateral flow immunoassay - Xia, Ji; Liu, Yifan; Ran, Menglin; Lu, Wenbo; Bi, Liyan; Wang, Qian; Lu, Dan; Cao, Xiaowei (RSC advances, 2020)
The accurate analysis of tumor related biomarkers is extremely critical in the diagnosis of the early stage cervical cancer. Herein, we designed a novel and inexpensive surface-enhanced Raman scattering-based lateral flow assay (SERS-based LFA) strip with a single test line, which was applied for the rapid and sensitive quantitative simultaneous analysis of SCCA and CA125 in serum samples from patients with cervical cancer. In the presence of target antigens, the monoclonal antibody-coupled and Raman reporter-labeled nano-Ag polydopamine nanospheres (PDA@Ag-NPs) aggregated on the test line modified by the polyclonal antibody to form a double-antibody sandwich structure. The finite difference time domain simulation demonstrated that large number of "hot spots" was generated among the nanogaps of aggregated PDA@AgNPs, which resulted in a huge enhancement of the signal of the Raman reporters. Accordingly, the limit of detection was determined to be 7.156 pg mL −1 for SCCA and 7.182 pg mL −1 for CA125 in phosphate buffer and 8.093 pg mL −1 for SCCA and 7.370 pg mL −1 for CA125 in human serum, revealing high sensitivity of this SERS-based LFA strip. Significantly, the detection of SCCA and CA125 using the SERS-based LFA was observed to have high specificity and reproducibility, and the whole detection was completed within 20 min. Furthermore, the SERS-based LFA and enzyme-linked immunosorbent assay were also employed in serum samples obtained from patients with cervical cancer, cervical intraepithelial neoplasia and healthy subjects, and perfect agreement existed between both the methods. Thus, clinically, the developed SERS-based LFA strip has strong potential for the simultaneous detection of multiple cancer biomarkers in serum. Based on SERS-based lateral flow immunoassay, nano-Ag polydopamine nanospheres was used for detecting squamous cell carcinoma antigen and cancer antigen 125 simultaneously in cervical cancer serum.